Nutritional Status, Bioactive Properties & Therapeutic Efficacy of Omega-3 Polyunsaturated Fatty Acids Obtained by Green Synthetic Routes - Mukesh Chander (International Journal of Nutritions, 2026)
Polyunsaturated fatty acids (PUFAs), particularly omega-3 (n-3) fatty acids like eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are crucial for human health. They support structural brain development, visual acuity, and cardiovascular function, while also exhibiting potent anti-inflammatory, antioxidant, and antimicrobial properties. Historically, marine fish oil has been the primary dietary source of these essential fatty acids. However, escalating concerns regarding ecological environmental impacts, the oceanic bioaccumulation of heavy metal contaminants, and the fundamental limits of global supply have spurred immense interest in the microbial production of PUFAs as a sustainable, land- based, and cost-effective alternative. This review synthesizes current knowledge on the nutritional, therapeutical and biological importance of omega-3 fatty acids and explores the distinct advantages of their microbial biosynthesis. We thoroughly examine the cellular mechanisms of oleaginous microorganisms, including marine microalgae, thraustochytrids, filamentous fungi (such as Mortierella species), and robust yeasts like Yarrowia lipolytica. Furthermore, recent breakthroughs in metabolic engineering and genetic manipulation,specifically the targeted overexpression of desaturase and elongase enzymes to overcome native lipid biosynthetic bottlenecks, have been critically assessed. Crucially, the integration of advanced bioprocess engineering to scale up single-cell oil production through the valorization of agro-industrial and horticultural wastes has been reviewed on the basis of post 2010 scietific data and research papers. Implementing abundant, low-cost substrates, such as sugarcane molasses, corn steep liquor, and fruit processing residues,not only substantially reduces fermentation costs but actively promotes a circular agricultural bioeconomy. We detail fermentation optimization strategies tailored to these complex carbon sources to maximize intracellular lipid accumulation. Finally, while discussing the safety and economic aspects of microbial PUFAs, this review outlines downstream processing metrics and provides a strategic roadmap for translating these vital biotechnological advances into commercial-scale, sustainable production and a potent therapeutic and nutritional source.
Keywords: Anti-inflammatory; Docosahexanoic acid; Eicosapentaenoic acid; antimicrobial; antioxidant; green synthesis; polyunsaturated fatty acids